Digital Tools in ESP Learning: Culturally and Linguistically Diverse Students' Practices and Challenges - Gumartifa, Asti; Syahri, Indawan; Alfaresi, Bengawan (Universitas Hamzanwadi, 2025)
Integrating digital technology in English for Specific Purposes (ESP) instruction has expanded opportunities for language learning, particularly for culturally and linguistically diverse (CALD) students in non-English major programs. However, limited research has explored how these learners use internet-based tools in localised university contexts. This study investigates the use of digital technology in ESP learning among CALD students at Universitas Muhammadiyah Palembang. Employing a descriptive mixed-methods design, data were gathered through questionnaires (n=505) and focus group discussions with ESP lecturers. Findings reveal that smartphones (53%) and laptops (28%) are the most commonly used devices, with tools such as Google Translate, Chatgpt, Zoom, and Grammarly supporting English learning inside and outside the classroom. Over 63% of students rated internet tools as “very useful” for accessing field-specific materials, and 44.65% identified technology as a primary companion to classroom instruction. Students also reported gains in language proficiency, self-regulated learning, and intercultural communication. Despite these benefits, students face persistent barriers, including limited digital skills (80.6%), insufficient device access (76.8%), slow internet (66.7%), and lack of technical support (63%). Nonetheless, 68.87% of students viewed technology as helpful for future learning, and half strongly believed it promotes learning flexibility. Students also called for improved digital training (44.65%) and infrastructure (33.02%). The findings highlight the need for targeted digital support and culturally responsive content to ensure inclusive and effective ESP instruction.